An EGFR-mutant lung adenocarcinoma that transformed into small-cell lung cancer. A case report - Chowaniecova, Gabriela; Berzinec, Peter; Kosturiakova, Gabriela; Plank, Lukas; Farkasova, Anna; Sekeresova, Monika; Juskanic, Dominik; Ondrus, Dalibor (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2022)
BACKGROUND: Transformation of EGFR (epidermal growth factor receptor) - mutant non-small cell lung cancer (NSCLC) into small-cell lung cancer (SCLC) is one mechanism of resistance to tyrosine kinase inhibitor (TKI) treatment, seen in approximately 3-10% cases. Such transformed SCLC often retains the original EGFR mutation (EGFRM), which is not otherwise observed in SCLC. CASE REPORT: We present a 67 y/o woman with pulmonary adenocarcinoma (AC) and EGFRM deletion on exon 19. After initial treatment with whole brain radiotherapy and 7 months of TKI afatinib, progression was observed. Liquid biopsy detected deletion on exon 19 and T790M mutation. Chemotherapy carboplatin plus pemetrexed was administered, with no response. Genetics from a rebiopsy of lung revealed deletion on exon 19. After 12 months treatment with TKI osimertinib, a progression in lung and pancreas lesions was detected, docetaxel was used, with followig progression. The lung biopsy revealed SCLC. Significant elevation of serum markers carcinoembryonic antigen (CEA) and neuron-specific enolase (NSE) was observed at the time of the SCLC diagnosis. Treatment with carboplatin and etoposide was not effective. The next biopsy found two populations of cells: SCLC and AC. The biopsy from the pancreatic lesion revealed metastasis of SCLC. PCR confirmed EGFRM deletion on exon 19 in the lung SCLC tissue sample. The following treatment lines of topotecan, erlotinib were not effective. The patient survived 36 months from diagnosis, 7 months from detection of SCLC. CONCLUSION: Screening for transformation of EGFR-mutant NSCLC to SCLC should be considered in resistance to TKI. In the presented case, this rare transformation was confirmed by histopathologic examination and by PCR. EGFRM in the lung SCLC, identical to that found in the original lung AC, was detected. Further, the observed elevation of serum tumor markers NSE and CEA can indicate this infrequent transformation and help to decide on rebiopsy.
Keywords: karcinoembryonální antigen; Carboplatin; Protein Kinase Inhibitors; EGFR mutation; ErbB Receptors; nádory plic; mutace; Adenocarcinoma of Lung; malobuněčný karcinom plic; karboplatina; chemorezistence; ženské pohlaví; nemalobuněčný karcinom plic; Mutation; Humans; Drug Resistance, Neoplasm; adenokarcinom plic; small-cell lung cancer; Carcinoembryonic Antigen; non-small cell lung cancer; Carcinoma, Non-Small-Cell Lung; erbB receptory; inhibitory proteinkinas; transformation; Small Cell Lung Carcinoma; Female; Lung Neoplasms; lidé